Post a New Question

Algebra

posted by on .

write in form y=a(x-h)^2+k

y=x^2-x-9
(x^2-2x)-9
complete the square
(x^2+2x+1-1)-9
(x^2+2x+1)-1-9
(x+1)^2-9

  • Algebra - ,

    -1 - 9 = -10
    also your -2x mysteriously turned into +2x

    so

    (x-1)^2 - 10

  • Algebra - ,

    y= x^2 -x - 9
    y=(x^2 -x + 0.5^2 - 0.5^2) -9 ; we get 0.5 by dividing 1 by 2)
    y=(x^2 -x + 0.25) - 0.25 -9
    y=(x-0.5)^2 - 9.25

  • Algebra - ,

    roro is correct, I misread your question

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question